The Duties of Non-Judicial Actors in Ensuring Competent Negotiation - Bibas, Stephanos (2013)
This essay, written for a symposium at Duquesne Law School entitled Plea Bargaining After Lafler and Frye, offers thoughts on how lawyers could learn from doctors’ experience in catching and preventing medical errors and aviation experts’ learning from airplane crashes and near misses. It also expresses skepticism about the efficacy of judges’ ex post review of ineffective assistance of counsel, but holds out more hope that public-defender organizations, bar associations, probation officers, sentencing judges, sentencing commissions, and line and supervisory prosecutors can do much more to prevent misunderstanding and remedy ineffective bargaining advice in the first place